Effect of tualang honey-mediated silver nanoparticles on TNF-α level, caspase-3 activity and hippocampal morphology in Kainic Acid-induced neurodegeneration in male rats - Hasim, Hidani; Kuttulebbai Naina Mohamed Salam, Sirajudeen; Rao, Pasupuleti Visweswara; Muthuraju, Sangu; Che Jalil, Nur Asyilla; Asari, Mohd Asnizam (IIUM Press, 2024)
INTRODUCTION: Despite being common disorder, the curative treatment for degenerative diseases are not yet available. Although Tualang honey (TH) has been reported to protect against neurodegeneration, but the effect of TH-mediated silver nanoparticles (THSN) on neurodegeneration is poorly understood. Thus, we conducted this study aimed to determine the effects of THSN on the levels of tumour necrosis factor alpha (TNF-α), caspase-3 activity, and hippocampal morphology in Kainic Acid (KA) induced neurodegeneration in rats. MATERIALS AND METHODS: A total of 72 Male Sprague Dawley rats were randomized into six groups which were the control, THSN 10mg, THSN 50 mg, KA only, KA+THSN 10 mg, and KA+THSN 50 mg groups. Each group was pre-treated orally with either distilled water or THSN (10 mg/kg or 50 mg/kg), according to their respective group. Following the last pre-treatment, each rat was injected with KA (15 mg/kg) or saline. After 24 h and 5 days of KA induction, all rats were sacrificed, and the hippocampus from each rat was harvested. Cresyl Violet and Fluoro Jade C staining were carried out to examine the number of viable cells and degenerating neurons. TNF-α level and caspase-3 activity in the hippocampus were measured using commercially available ELISA kits. RESULTS: Rats with KA-induced neurodegeneration demonstrated a significant increase (p<0.05) of TNF-α level and caspase-3 activity with a lower number of viable cells and increased number of degenerating neurons in the hippocampus. The pre-treatments of THSN groups improved these changes by lowering the TNF-α level and caspase-3 activity and decreasing the number of degenerating neurons. CONCLUSION: THSN could have potential neuroprotective effects in ameliorating TNF-α level, caspase-3 activity, and hippocampal damage in KA-induced male rats.